PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 007 SIMANDOLAK KECAMATAN BENAI KUANTAN SINGINGI - Nopri Ardian; Hendri Marhadi; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research was conducted because of the result of learning science study class V SD Negeri 007 Simandolak. KKM achieved by school was 75. From 19students who achieve KKM just 7 students (36,84%) while students who did’nt achieve KKM is 12 students (63,16%) with a class average of 62,37. The purpose of this research to improve learning outcomes IPS class V SD Negeri 007 Simandolak, with the application of problem based learning. The results obtained by the average value of 62,37 basic score increased in the first cycle of 8,02% to 67,37. In the second cycle the average value of students also increased by 24,88% to 77,89. On the basic of classical completeness score IPS student learning outcomes is only 36,84% (not finished). After the professor of applied based model problem based learning in the first cycle classical completeness increased to 57,89% (not finished), and the second cycle of classical completeness obtained are increased to increase to 84,21%. Activities of teachers at the first meeting of first cycle acquire a percentage of 65% with enough categories. The second meeting increased to 75% in enough categories. In the first meeting of second cycle increased to 85% with good category. At the second meeting increased to 90% with good category. Activities of students in the first meeting of the first cycle acquire a percentage of 65% with enough categories. The second meeting increased to 70% in enough categories. In the first meeting of the second cycle increased to 80% with good category. At the second meeting increased to 85% with good category. From this research can be concluded that by applying model of study based on problem can improve result of study of IPS student of class V Sd Negeri 007 Simandolak.Keywords: Based on the problem, learning outcomes IPS